Male ant reproductive investment in a seasonal wet tropical forest: Consequences of future climate change - Donoso, David A; Basset, Yves; Shik, Jonathan Z; Forrister, Dale L; Uquillas, Adriana; Salazar-Méndez, Yasmín; Arizala, Stephany; Polanco, Pamela; Beckett, Saul; Dominguez G, Diego; Barrios, Héctor (PloS one, 2022)
Tropical forests sustain many ant species whose mating events often involve conspicuous flying swarms of winged gynes and males. The success of these reproductive flights depends on environmental variables and determines the maintenance of local ant diversity. However, we lack a strong understanding of the role of environmental variables in shaping the phenology of these flights. Using a combination of community-level analyses and a time-series model on male abundance, we studied male ant phenology in a seasonally wet lowland rainforest in the Panama Canal. The male flights of 161 ant species, sampled with 10 Malaise traps during 58 consecutive weeks (from August 2014 to September 2015), varied widely in number (mean = 9.8 weeks, median = 4, range = 1 to 58). Those species abundant enough for analysis (n = 97) flew mainly towards the end of the dry season and at the start of the rainy season. While litterfall, rain, temperature, and air humidity explained community composition, the time-series model estimators elucidated more complex patterns of reproductive investment across the entire year. For example, male abundance increased in weeks when maximum daily temperature increased and in wet weeks during the dry season. On the contrary, male abundance decreased in periods when rain receded (e.g., at the start of the dry season), in periods when rain fell daily (e.g., right after the beginning of the wet season), or when there was an increase in the short-term rate of litterfall (e.g., at the end of the dry season). Together, these results suggest that the BCI ant community is adapted to the dry/wet transition as the best timing of reproductive investment. We hypothesize that current climate change scenarios for tropical regions with higher average temperature, but lower rainfall, may generate phenological mismatches between reproductive flights and the adequate conditions needed for a successful start of the colony.
Keywords: Animals; stromy; tropické klima; Forests; Climate Change; Seasons; mužské pohlaví; Formicidae; zvířata; Male; Trees; Tropical Climate; Ants; déšť; roční období; klimatické změny; Rain; lesy